Sistem Pendukung Keputusan Kelompok Untuk Menentukan Penerima AGC Award Menggunakan Metode Simple Additive Weighting dan Borda - Arif Tirtana (Jurnal Informatika: Jurnal Pengembangan IT, 2019)
PT. Astra International continues to develop into one of the leading group of companies in Indonesia. Currenty its manages six core business namely, automotive, financial, services, heavy equipment, mining, agro-business, infrastructure, logistics, and information techonology. In its operations can bring various impact on enviroment quality, such as the avalaibility of natural resources (water, energy and materials), waste generated in the form of solid, fluid, and air. Therefore ESR Division carry out an assessment of the subsidiary programs to minimize the impact. In this research using SAW method to support the decision making of individual decision, and Borda method to support the group decision making and to determine AGC Award recipient. The decision support system model proposed in this study has proven to solve problems that require individual or group decision-making processes.